Needs Analysis of Multimodal-Based Reading Comprehension Teaching Materials for Level A1 French Language Education Study Program Students - Ekowati, Sri Harini; Andika, Yunilis (Universitas Majalengka, 2024)
This study aims to obtain information about French Language Education Study Program students' perception of using multimodal texts in Réception Écrite (RE) learning or reading, followed by a needs analysis of multimodal text-based teaching materials. Réception Écrite learning is currently carried out using the book Alter Ego Plus A1. The book is not multimodal. Therefore, it is necessary to develop teaching materials for multimodal-based Réception Écrite courses. Questionnaires were employed to get students' perceptions of the need for multimodal-based Réception Écrite teaching materials. The respondents to this questionnaire were 40 students for the 2021 academic year. The questionnaire employed has been validated by experts. The data obtained from the questionnaire were analyzed using descriptive statistics by calculating percentages. Generally, students already knew and understood a multimodal text. However, in the Réception Écrite course, only 40% of students studied multimodal texts. Students agreed to the use of multimodal texts. They needed multimodal-based Reception Ecrite teaching materials because, currently, there were no multimodal-based textbooks in the French Language Education Study Program. The development of multimodal-based teaching materials in the Réception Écrite course in the French Language Education Study Program must be carried out because this learning provides many benefits to students and lecturers. Benefits for students include interesting, easy to understand, not boring, encouraging students, fun, and others